Interaction of Oral and Toothbrush Microbiota Affects Oral Cavity Health - Shang, Qingyao; Gao, Yuan; Qin, Ting; Wang, Shuai; Shi, Yan; Chen, Tingtao (Frontiers in Cellular and Infection Microbiology, 2020)
Brushing teeth is necessary for people to maintain oral health, while little work is done to explore the microbial diversity in toothbrush and study the potential impact of these bacteria on human health. In the present study, 20 participants were enrolled, and the microbial diversity in their oral cavity and toothbrush were investigated using high-throughput sequencing. Our results indicated that 1,136 and 976 operational taxonomic units (OTUs) were obtained from groups CB (sample from toothbrushes using traditional Chinese medicinal toothpaste) and AB (sample from toothbrushes using antibacterial toothpaste), and pathogens Acinetobacter baumannii, Staphylococcus aureus, Candida albicans, had also been identified from toothbrush, which increased the chance for host to get infectious diseases, neurodegenerative diseases, cardiovascular diseases, and cancers. Moreover, our in vitro results indicated that the traditional Chinese medicinal toothpaste and antibacterial toothpaste could not only inhibit the growth of pathogens, but also markedly inhibited the growth of probiotics Lactobacillus salivarius and Streptococcus salivarius. Therefore, the inhibited effect of toothpaste on probiotics, together with the existing of pathogens in toothbrush, indicating a potential risk of brushing teeth on people with sub-health state.